2021
DOI: 10.1038/s41398-021-01205-0
|View full text |Cite
|
Sign up to set email alerts
|

Altered offspring neurodevelopment in an arginine vasopressin preeclampsia model

Abstract: Preeclampsia is a severe gestational hypertensive condition linked to child neuropsychiatric disorders, although underlying mechanisms are unclear. We used a recently developed, clinically relevant animal model of preeclampsia to assess offspring. C57BL/6J mouse dams were chronically infused with arginine vasopressin (AVP) or saline (24 ng/h) throughout pregnancy. Adult offspring were behaviorally tested (Y-maze, open field, rotarod, social approach, and elevated plus maze). Offspring brain was assessed histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 67 publications
2
30
1
Order By: Relevance
“…The neurobiology of cognitive alterations in offspring of mothers with PE 7,53,54 is poorly understood. 55 Compatible with described alterations in brain perfusion, we also found a differential expression of angiogenic proteins that participate in signaling pathways such as inflammation, cancer, cellular stress, senescence, and apoptotic in the pup's brain of RUPP mice. In PE, cellular senescence, apoptosis resistance, and pro-inflammatory phenotype have been related mechanistically to mesenchymal stem cell dysfunction.…”
Section: Discussionsupporting
confidence: 65%
“…The neurobiology of cognitive alterations in offspring of mothers with PE 7,53,54 is poorly understood. 55 Compatible with described alterations in brain perfusion, we also found a differential expression of angiogenic proteins that participate in signaling pathways such as inflammation, cancer, cellular stress, senescence, and apoptotic in the pup's brain of RUPP mice. In PE, cellular senescence, apoptosis resistance, and pro-inflammatory phenotype have been related mechanistically to mesenchymal stem cell dysfunction.…”
Section: Discussionsupporting
confidence: 65%
“…Infusions of AVP during pregnancy increased IL-17 levels in maternal plasma and the placenta (248), suggesting that IL-17 may also affect fetal brain development following AVP loading. To date, however, only one study has reported neurological and behavioral consequence of AVP-infused HDP in offspring (249).…”
Section: Vasopressinmentioning
confidence: 99%
“…Infusions of AVP during pregnancy increased IL-17 levels in maternal plasma and the placenta ( 248 ), suggesting that IL-17 may also affect fetal brain development following AVP loading. To date, however, only one study has reported neurological and behavioral consequence of AVP-infused HDP in offspring ( 249 ). Both male and female offspring that were exposed to AVP on P7 had a smaller neocortex, but caudate-putamen volume decreased in males only and increased relative to the neocortex in females.…”
Section: Hypertensive Disorders Of Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…There has been much recent interest in using rodent models to examine the brain and behaviour of offspring prenatally exposed to PE. These have yielded valuable insights into the effects of a PE-like insult on mammalian neurodevelopment, which include alterations in neuro-and gliogenesis, regional brain volumes, forebrain transcriptional pro le, and pronounced behavioural de cits [15][16][17][18]. However, there is a need to understand whether exposure to PE affects neuronal development at a single cell level, particularly in human cells.…”
Section: Introductionmentioning
confidence: 99%